Deep space observation satellites - Sherman, Josepha. frey50 (New York : Rosen Pub. Group, 2003)
A chronological presentation of the launching of satellites for observation of the solar system and deep space, with a discussion of what we have learned from such satellites.
1957-1967 -- 1968-1978 -- 1979-1989 -- 1990-2000, the future.
Keywords: Space probes -- History; Orbiting astronomical observatories -- History; Orbiting astronomical observatories; Outer space -- Exploration